Pemanfaatan Cangkang Gonggong untuk Meminimalkan Limbah Penyebab Polusi menjadi Hiasan Bunga Mini - Nelson, Alden; Wen, Wel; Istiqomah, Nurul; Chrisderry, Chrisderry; Selvianti, Selvianti; Setiawan, Setiawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
The use of gonggong shells can be an alternative in increasing business for MSMEs. Utilizing gonggong shells is the main objective of carrying out this activity and this can reduce pollution caused by gonggong shell waste. The method of implementing this activity is through direct observation and interviews. By innovating from gonggong shells, mini flower decorations have become one of the efforts to stimulate the creative economy and minimize waste that causes pollution.